2000
DOI: 10.1002/(sici)1097-0215(20000215)85:4<527::aid-ijc14>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Late apoptotic effects of taxanes on K562 erythroleukemia cells: Apoptosis is delayed upstream of caspase‐3 activation

Abstract: The efficacy of taxanes on human leukemia cells is the object of intensive in vitro investigation concerning the influence of cell‐type‐specific characteristics on cytotoxic response to drugs. The present study dissects the response to taxanes of HL60 acute myelomonocytic leukemia and of K562 chronic myelogenous leukemia, in parallel over a 72‐hr time‐span. The kinetics of cytotoxicity following pulsed and continuous exposure to either taxol or taxotere showed a delayed response of K562 cells independently of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Our present results showed the dose-and time-dependency of the antitumor effects of paclitaxel on these two types of leukemia cells, and the potency of paclitaxel in K562 cells was stronger than in MEL cells. Paclitaxel clearly induced apoptosis in K562 cells, which is in accordance with previous results (21). Also, there was a significant arrest of cell cycle to G 2 /M phase induced by paclitaxel in K562 cells, similar to the findings of a previous report (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present results showed the dose-and time-dependency of the antitumor effects of paclitaxel on these two types of leukemia cells, and the potency of paclitaxel in K562 cells was stronger than in MEL cells. Paclitaxel clearly induced apoptosis in K562 cells, which is in accordance with previous results (21). Also, there was a significant arrest of cell cycle to G 2 /M phase induced by paclitaxel in K562 cells, similar to the findings of a previous report (26).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed the efficacy of taxanes on human leukemic cell lines (16,(19)(20)(21), as well as their effectiveness in inducing apoptosis in vivo (22) and in fresh leukemia cells in primary cultures (23). However, to the best of our knowledge, there is no report on the effect of paclitaxel on leukemia induced by virus.…”
Section: Discussionmentioning
confidence: 99%
“…However, in K562 cells, which are tolerable to many apoptosis-inducing agents, p38 MAPK was not activated and apoptotic cell death was not observed after 8-Cl-cAMP treatment. The mechanisms by which the BCR-ABL-positive leukemia cells resist the apoptotic signals are not fully understood, although delayed caspase activation or increased Bcl-X L level in K562 cells has been reported (32). We showed here that p38 MAPK activation can be regarded as another determinant to execute apoptosis in leukemia cells.…”
Section: Discussionmentioning
confidence: 60%
“…However, K562 (chronic myelogenous leukemia) was more resistant to the growth inhibitory effect of 8-Cl-cAMP than HL60. It has been reported that K562 cells express the BCR-ABL fusion protein due to genetic rearrangement that maintains resistance to apoptosis induced under various conditions (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, HL60 cells undergo apoptosis in response to chemotherapeutic agents with diverse mechanisms of action: doxorubicin (DOX) and etoposide (topoisomease-II inhibitors), paclitaxel (PTX; microtubule active agent), flavopiridol (FL; an inhibitor of transcription) and proteasomal inhibitors. [1][2][3][4][5][6] In contrast, apoptosis-reluctant cells, including common cancer cell lines, undergo either slow (nonapoptotic) types of cell death or cycle arrest. 7 For example, K562 leukemia cells are apoptosis reluctant, because they express the Bcr-Abl antiapoptotic kinase, which in turn induces heat-shock protein-70 (Hsp70).…”
Section: Introductionmentioning
confidence: 99%